Using Failure Analysis Learning in Business School Instruction - Gary OSTER (Revista de Management Comparat International)
Most university business schools logically use best practices learning so students may learn professional policies and procedures generally accepted by business and industry as being correct and effective. Whether through tradition, historical precedent, or instructor preference, errors and faults in leaders, systems, or products are rarely considered. Conversely, failure analysis learning is a pedagogical methodology that requires the systematic collection and analysis of information to determine the root causes of a specific failure, and the development and reporting of recommendations to prevent the failure from recurring in the future. Failure analysis learning includes a form of behavioral systems analysis and deals with the unwanted behavior of systems. In most cases, failure analysis learning is composed of five important steps, including data gathering, data analysis, conclusion development, countervailing recommendations, and extrapolation to other circumstances. What differentiates failure analysis learning from other forms of study is that it is widely inclusive of all facts and speculation related to a failure, systematic in the gathering, measurement, and consideration of this information, and thoroughly prescriptive in reporting proposed actions relative to failure prevention. Failure analysis learning includes forensic inquiry utilizing the collection and analysis of data and the use of rigorous scientific methodologies to determine the root causes of failure, and then the intentional extrapolation of findings to other circumstances through the use of analogy and metaphor. Failure analysis learning is most often focused on aircraft, infrastructure, buildings, vehicles, leadership, equipment, processes, etc. As a minimally-guided learning methodology, failure analysis learning is a pedagogically sound tool through which to impart key business concepts.